Wave Energy Potential Using OWC (Oscillating Water Column) System at Pantai Baron, Gunung Kidul, DI Yogyakarta, Indonesia - Kurniawan, Aries Taufiq (Semarak Ilmu Publishing, 2022)
The southern coast of Yogyakarta province in Indonesia has large potential for wave energy, where the most ideal location is Pantai Baron. This research was conducted to study the potential wave energy using OWC (Oscillating Water Column) at Pantai Baron. Wave height and wave periods are needed to find the potential wave energy that can be generated. Wind, fetch and bathymetry data will be used to determine wave height in deep sea. Refraction and shoaling calculation will be used to calculate wave height in shallow depth area. Wave height after refraction-shoaling combine with tidal data will be used to determine optimum position for OWC system. Wave height, wave incoming direction, total efficiency for OWC system and capacity factor will be used to calculate potential wave energy that can be produced. Average wave height on deep sea is 1.08 m, wave period is 9.73 sec and incoming wave dominant is from east. Optimum depth of system OWC is -5.0 m below MSL. Average wave height after refraction and shoaling effect is 1.1 – 1.2 m. Potential wave energy that can be generated is 3.9 – 5.6 MWh per year per 1 OWC system with chamber width is 2.4 m. © 2023,International Journal of Information Science and Management.All Rights Reserved.